A SOUTH AFRICAN FOOD SECURITY CHALLENGE: THE CRITIQUE OF INITIATIVES AT HOUSEHOLD LEVEL - Fanelesibonge Masinga; Thanyani S Madzivhandila (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The food security challenge has affected many households in South Africa, as some households struggle to maintain a healthy diet and adequate food access. Many households in South Africa experience food hunger and starvation, in particular households in rural areas which is often characterised by large family groups. The pressing challenge encountered by policy makers is ensuring that all households in South Africa are food secure, as it stands this has not been achieved. Despite pro-active initiatives such as the Integrated food security, nutrition program, zero hunger programme and social grants, households in South Africa continue to be negatively impacted by food insecurity, especially in the awake of climate change. The paper aims to argue that food security challenges faced by households in South Africa could be addressed if strategies are formulated not only to secure the individual but the entire household. The paper analyses three literature themes namely: food security globally, accessed food security challenges in South Africa and finally critiqued food initiatives that potentially play a role in household food security. The findings of the paper conclude that food security initiative programs are available in South Africa, however they often rely on monetary terms of ensuring food security, the social grants for example are targeted to some household members not everyone in the household. The paper suggests that targeting certain household members is not a comprehensive approach in addressing food security at household level. Lessons drawn from literature, provide a way forward towards policy effective and efficient interventions that seek to foster household food security interventions while observing nature-based agro-forestry initiatives that are community-led.